Non-coronary atherosclerosis: a marker of poor prognosis in patients undergoing coronary artery bypass surgery - González-Lorenzo, Óscar; Franco Pelaez, Juan A.; Kallmeyer, Andrea; Nieto, Luis; Esteban, Laura; Pello, Ana; Aceña, Álvaro; Aldamiz, Gonzalo; Tuñón, José (Frontiers in Cardiovascular Medicine, 2024)
Introduction: The presence of non-coronary atherosclerosis (NCA) in patients with coronary arte¬¬ry disease is associated with a poor prognosis. We have studied if NCA is also a predictor of poorer outcomes in patients undergoing coronary artery bypass grafting (CABG). Materials and Methods: Observational study involving 567 consecutive patients who underwent CABG. Variables and prognosis were analysed according to the presence or absence of NCA, defined as: previous stroke, transient ischemic attack (TIA), or peripheral artery disease (PAD) (lower extremity artery disease [LEAD], carotid disease, previous lower limb vascular surgery or abdominal aortic aneurysm [AAA]). The primary outcome was a combination of TIA/stroke, acute myocardial infarction, new revascularization procedure or death. The secondary outcome added the need for LEAD revascularization or AAA surgery. Results: One-hundred thirty-eight patients (24%) had NCA. Among them, traditional cardiovascular risk factors and older age were more frequently present. At multivariate analysis, NCA (Hazard Ratio [HR]=1.84, (95% confidence interval [CI] 1.27-2.69), age (HR=1.35, (95%CI 1.09–1.67), p=0.004), and diabetes mellitus (HR=1.50, (95%CI 1.05–2.15), p=0.025), were positively associated with the development of the primary outcome, while estimated glomerular filtration rate (HR=0.86, (95%CI 0.80–0.93), p=0.001) and use of left internal mammary artery (HR=0.36, (95%CI 0.15–0.82), p=0.035), were inversely associated with this outcome. NCA was also an independent predictor of the secondary outcome. Mortality was also higher in NCA patients (27.5% vs 9%, p<0.001). Conclusions: Among patients with CABG, the presence of NCA doubled the risk of developing cardiovascular events, and it was associated with higher mortality.